Exploring the Ayurvedic Understanding and Management of Madatyaya: A Scoping Review - Muttungha Valappil Shibna; Manoj Kumar Patel; Shivakumar S. Harti (Journal of Ayurveda, 2025)
Background: Madatyaya, a condition described in Ayurveda, results from excessive alcohol consumption and leads to significant physical, psychological, and social consequences. Individuals with alcohol use disorders often seek traditional, complementary, and integrative approaches, including Ayurveda, for management and rehabilitation. Understanding the current evidence base for Ayurvedic interventions in Madatyaya is crucial to identify therapeutic potentials and guide future research in this field. Objectives: This scoping review aims to explore the evidence on the Ayurvedic management of Madatyaya, and to identify research gaps and future research potential. Eligibility Criteria: Includes all published full-text studies on Madatyaya – covering Ayurvedic principles, diagnosis, and management through herbal, purificatory, dietary, or lifestyle interventions without restrictions on language or publication year, and includes clinical, preclinical, and observational studies. Data Sources: Electronic databases, such as PubMed, Cochrane Library, AYUSH Research Portal, Digital Helpline for Ayurveda Research Articles, and Google Scholar. Review Methods: After searching databases, data from eligible studies were extracted, summarized, and documented using the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews guidelines. Results and Conclusion: Sixty-eight records were identified, 23 articles included in the scoping review for final data extraction, synthesis, and to prepare a narrative summary. In this scoping review, only seven randomized controlled trials were identified, indicating a need for more research publications to synthesize evidence. Future research should expand interventions, explore Ayurveda’s role alongside biomedical treatments, assess diverse outcome measures, and enhance safety reporting.